Stavsager Høj ved Fæsted – de bronzealderlige aktivitetsspor og deres atypiske karakter . - Grundvad, Lars; Egelund Poulsen, Martin (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
The Iron Age weapon deposits at Fæsted have previously been presented at Arkæologi i Slesvig, but since then three more campaigns have been excavated at the site which is rightfully called Stavsager Høj. These later excavations have yielded numerous spectacular discoveries, and the focus has long been on the Iron Age finds. But in fact, the site has also revealed much older artefacts and structures from the Bronze Age. These older discoveries will be the focus here, because they also deserve to be presented as they represent remains that, in some cases, may have no Danish parallels. It has long been known that the region around Stavsager Høj is visually characterized by a distinctive row of burial mounds stretching from the south to the north, several of which have been found to contain rather rich grave goods. Stavsager Høj is one of these mounds. However, the recent archaeological excavations have revealed structures that, together with the mounds, testify to a landscape of special significance as early as the Early Bronze Age. The excavated archaeological remains are seen in the shape of a number of extensive oval ditch structures, which are ¹⁴C-dated to around 1500 BC. Furthermore, cooking pit assemblages are seen in the form of both cooking pit ditches and clusters, which also testifies to an atypical use of the landscape. The purpose of this article is to present these Early Bronze Age discoveries, to place them in their landscape context, and to provide an interpretation of their use – are these discoveries evidence of religious practice and gatherings, or are they evidence of secular aspects that just have not been observed at contemporary sites?